The mysterious Benedict Society - Stewart, Trenton Lee (Stewart, Trenton Lee. Mysterious Benedict Society series., 2007)
After passing a series of mind-bending tests, four children are selected for a secret mission that requires them to go undercover at the Learning Institute for the Very Enlightened, where the only rule is that there are no rules.